Gender-Work Identity Management at Work and within Work-Life Boundaries - CHENG, Chi-Ying (Institutional Knowledge at Singapore Management University, 2013)
Gender is usually an easily observed and salient characteristic of a person’s identity and one that impacts their experience at work. Occupations (e.g., Treimen & Terrell, 1975), organizational positions such as managerial roles (e.g., Heilman, 2001), and tasks like negotiation (e.g., Stuhlmacher & Walters, 1999) are sex-typed (i.e., associated with males or females). The gender identity of individuals impacts their work; but additionally, individuals’ perception of how compatible their gender identity is to their professional identity—their within-person gender-professional identity integration—impacts important organization and work-life outcomes (Cheng, Sanchez-Burks, & Lee, 2008). This four-paper symposium focuses on gender identity as both a between- and within-person construct. First, Wallen, Mor, and Devine explore whether male nurses’ gender-professional identity integration lessens the negative impact men experience working in a female-typed occupation. Cheng and Tan, in the second paper, use laboratory experiments to investigate how gender- professional identity integration impacts female negotiators’ prosocial tendencies and integrative negotiation performance. Third, Ellen Kossek focuses on the work-life boundary, offering a theoretical structure for how individuals’ identities lead them to create and navigate work-life boundaries and experience important work-life outcomes. And fourth, Paddock and Cheng adapt the concept of gender-professional identity integration in the first two papers to introduce a measure of family-professional identity integration, examining this measure’s fit within the existing work-life literature, including elements discussed in the third paper. Finally, Ellen Kossek will comment on the four papers and discuss the importance of gender identity at work and as individuals navigate work-life boundaries.